Distribution Pattern of ELF Field Exposure Electricity Distribution Substation Portal Pole Type 20 kV Medium Voltage Network - Utoyo, Ega Bonansyah; Prihandono, Trapsilo; Sudarti, Sudarti (Department of Physics Education, Universitas Mataram, 2024)
The electricity distribution substation is one of the components of the electricity distribution system. Electrical distribution substations, especially portal pole-type electrical distribution substations, can emit ELF fields. However, people need to be aware of the health risks of ELF fields and continue to carry out various activities near electricity distribution substations. This research aims to create a distribution pattern for ELF Field and determine its safety level based on WHO thresholds. The research was conducted in the Jember Regency, particularly in Sumbersari District. This research uses a portal pole-type electricity distribution substations. The substation criteria studied were a portal pole distribution substation on a 20 kV transmission line with a transformer capacity of 160 kVA. The measurement points are 0 m below the transformer, 0.7 m, 1.4 m, 2.1 m, 2.8 m, 3.5 m, 4.1 m, and 4.9 m from the distribution substation building at a height of 1.5 m from the ground for three days at 21.00 WIB and 30 measurements were taken. The distances of these points to the transformer are 4.256 m, 4.313 m, 4.480 m, 4.745 m, 5.094 m, 5.510 m, 5.979 m and 6.490 m respectively. The type of research used is quantitative research with survey data collection techniques. The research design used was cross sectional study. Cross sectional study is a type of observational research design that collects data at one specific point in time from a sample which represents the population studied. ELF field measurements show a spherical distribution pattern with an average magnetic field intensity between 0.0358 µT and 2.91 µT and an average electric field intensity between 2.35 V/m and 16.42 V/m. The magnitude of the magnetic field and electric field measured gets smaller as the distance from the measurement point increases. According to WHO, these results are below the threshold for the general group. This research concludes that the portal pole-type distribution substation in the medium voltage network produces a safe ELF field with a spherical distribution pattern that is inversely proportional to the distance.